Intention to use m-government services among consumers in Putrajaya - Ishak, Maizatul Aqira; Muhammad Arif, Afida Mastura (Kementerian Perdagangan Dalam Negeri dan Hal Ehwal Pengguna, 2019)
The primary aim of this study is to identify the relationship between selected factors and the intention to use m-government services among consumers. The study employs the Pearson correlation analysis to test the Technology Acceptance Model (TAM) by incorporating the factors of perceived usefulness, perceived ease of use and perceived trustworthiness. The research is based upon a self-administrated questionnaire survey of 200 consumers in Putrajaya.. The outcome revealed a significant and positive relationship between perceived usefulness, perceived ease of use and perceived trustworthiness with the intention to use m-government services. The findings of this study should enable m-government service providers to better understand the factors that can attract the consumers’ intention to use m-government services. This can be done by enhancing the ease of use and usefulness of the services.